Renal damage in hypertensive patients: primary healthcare units study in Braga region (Portuguese Journal of Family Medicine and General Practice, 2018)
Introduction: Hypertension maybe cause or consequence of chronic kidney disease (CKD). High blood pressure can change albumin excretion rate and/or lead to more rapid decline of glomerular filtration rate (GFR).Objetive: Determine the prevalence of the microalbuminuria (MA) and CKD in patients with hypertension of two Northern Portuguese Primary Health Care Providers. Verify the relationship between individual factors and MA/CKD.Methods: Adults diagnosed with arterial hypertension were included in this study. Data collection from MIM@UF and SClínico programs, during 2015. Variables: age, gender, body weight, blood pressure control, length of disease, diabetes mellitus and renin angiotensin inhibitor drugs users. Then a binary logistic regression model was created to identify possible risk factors associated with MA and CKD.Results: The study included 310 individuals with arterial hypertension, mostly women (51,9%) with average age of 68,1 years. MA was present in 10,6%, preferentially determined by 24 hours urine collection (54,5%). The prevalence of CKD with GFR
Keywords: Hypertension; Albuminuria; Chronic kidney disease; Primary Health Care.